Development of an Android-based Learning Media Application for Visually Impaired Students - Azmi, Nurul; Maryono, Dwi; Yuana, Rosihan Ari (Universitas Sebelas Maret, 2017)
This research aims to develop the English for Disability (EFORD) application, on Android-based learning english media for Visually Impaired students and determine its based this on assessment of matter expert, media expert, special needs teacher and students. The research method adopted in this research is Research and Development (R&D). The development of this application through five phases: (1) Analysis of problems, through observation and interviews. (2) Collecting information as product planning / analysis of the needs of the media as required of blind children. (3) The design phase of products such as the manufacture of flow and storyboard navigation map.(4) Design validation phase form of an expert assessment of the media is developed. (5) testing products phase, such as assessment of the application by blind students. The results of this research is EFORD application which is feasible to be used as English learning media for visual impairment application based on assessment: 1)Media expert it's obtained a percentage scored 95%, include for very worthy category, 2)Subject matter, expert its obtained percentage scored 75% include for worthy category and 3) Special needs teacher it's obtained a percentage scored 83% include for very worthy category. Upon demonstration, students indicated the positive response of ≥ 70% in each indicator. Therefore English learning media with Android based application English for Disability (EFORD) is very feasible to be used as an English learning media especially grammar and speaking English content for students of visual impairment for a number of reasons.This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.